INNER-CORE ANISOTROPY AND ROTATION - Tromp J. (My University, 2001)
This paper reviews recent research focused on the Earth's inner core. Large inner-core traveltime anomalies and the anomalous splitting of core-sensitive free oscillations strongly suggest that the inner core is anisotropic. Initial models involved a simple, constant or depth-dependent cylindrical anisotropy at a level less than a few percent. Recent observations suggest that its eastern hemisphere is largely isotropic, whereas its western hemisphere is highly anisotropic, and there are indications that its top 100 km may be isotropic. The coda of inner-core reflected phases has been used to infer strong heterogeneities with a length scale of just a few kilometers. Thus, a complicated three-dimensional picture of the inner core is beginning to emerge, although it has been suggested that much of this complexity may be the misinterpretation of signals that have their origin in the lowermost mantle. Numerical models of the geodynamo suggest that the inner core may rotate at a slightly different rate than the mantle. Recent seismological estimates based upon traveltime and normal-mode data limit inner-core differential rotation to less than +0.2 degrees per year.